2010
DOI: 10.1021/jf102053h
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Simple Droplet Sampling of Sap from Plant Tissues and Capillary Microextraction of Soluble Saccharides for Picogram-Scale Quantitative Determination with GC-MS

Abstract: Soluble saccharides are very important metabolites of the life cycle and synthesis of structural polysaccharide components (cellulose, hemicellulose, pectin, etc.) of cell walls. A new method for droplet sampling of saps from tissues of organisms and manipulation routines in capillaries for extraction, derivation, and partitioning were developed for picogram-scale quantitative determination with gas chromatography-mass spectrometry (GC-MS). Five to ten microliters of sap was sampled with a glass capillary cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…More recently, Malagon et al and Zhang et al detected rhamnitol in human urine using GC/MS (Malagon et al, 2006) and LC/MS with HILIC (Zhang, Creek, Barrett, Blackburn, & Watson, 2012). Rhamnitol was detected in the leaves of Arabidopsis thaliana, corn grains (Zea maize), and the fruit of cucumber (Cucumis sativus) by GC/MS; however, it was not found in Fuji apples, in contrast to our results (Li et al, 2013;Tan et al, 2010). In the only study of fruits, Yun et al identified rhamnitol in Satsuma mandarin (Citrus unshiu Marcovitch) (Yun et al, 2013).…”
Section: Apple Characterisation By Targeted Analysis With Annotated Mcontrasting
confidence: 86%
“…More recently, Malagon et al and Zhang et al detected rhamnitol in human urine using GC/MS (Malagon et al, 2006) and LC/MS with HILIC (Zhang, Creek, Barrett, Blackburn, & Watson, 2012). Rhamnitol was detected in the leaves of Arabidopsis thaliana, corn grains (Zea maize), and the fruit of cucumber (Cucumis sativus) by GC/MS; however, it was not found in Fuji apples, in contrast to our results (Li et al, 2013;Tan et al, 2010). In the only study of fruits, Yun et al identified rhamnitol in Satsuma mandarin (Citrus unshiu Marcovitch) (Yun et al, 2013).…”
Section: Apple Characterisation By Targeted Analysis With Annotated Mcontrasting
confidence: 86%
“…Levels of seed soluble monosaccharides (sucrose, glucose and fructose) were measured by gas chromatography mass spectrometry (GC–MS) analysis as previously reported (Tan et al 2010 ; Li et al 2013 ) with some modifications. Briefly, 200 mg flour samples were dissolved in 2 mL Me 2 SO, mixed with 150 μL of acetic anhydride and 30 μL of 1-methylimidazole, and stirred for 10 min in glass tubes; 600 μL of double-distilled H 2 O (ddH 2 O) was added to each tube to remove excess acetic anhydride, and 100 μL of CH 2 Cl 2 was added to extract the acetylated derivatives.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose, fructose, galactose, and sucrose in flag leaf blade, internode and panicle of WT and mutant plants were extracted with 80% methanol and quantified by GC-MS analysis as previously described (Tan et al 2010).…”
Section: Determination Of Sugar Contentsmentioning
confidence: 99%